Video-assisted thoracoscopic surgery for retained hemothorax in blunt chest trauma. Issue 4 (July 2015) - Chou, Yi-Pin; Lin, Hsing-Lin; Wu, Tzu-Chin
Abstract : Purpose of review: In the last decade, video-assisted thoracoscopic surgery (VATS) has become a popular method in diagnosis and treatment of acute chest injuries. Except for patients with unstable vital signs who require larger surgical incisions to check bleeding, this endoscopic surgery could be employed in the majority of thoracic injury patients with stable vital signs. Recent findings: In the past, VATS was used to evacuate traumatic-retained hemothorax. Recent study has revealed further that lung repair during VATS could decrease complications after trauma. Management of fractured ribs could also be assisted by VATS. Early VATS intervention within 7 days after injury can decrease the rate of posttraumatic infection and length of hospital stay. In studies of the pathophysiology of animal models, N -acetylcysteine and methylene blue were used in animals with blunt chest trauma and found to improve clinical outcomes. Summary: Retained hemothorax derived from blunt chest trauma should be managed carefully and rapidly. Early VATS intervention is a well tolerated and reliable procedure that can be applied to manage this complication cost effectively.